The Injection Extract of Batik Spinach (Amaranthus bicolor) By Different Doses Into Mud Crabs (Scylla Serrata) - Desi Nurcahaya Lumbantoruan; Rusliadi Rusliadi; Niken Ayu Pamukas (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This research was conducted in Canang Kering Village, XX environment of Belawan Canang, Medan Belawan, Medan City, North Sumatra Province. This study aims to determine the effect of injection of batik spinach extract (Amaranthus bicolor) in accelerating molting, specific growth rate and survival rate of mud crabs (Scylla serrata). This research was conducted using Experimental Methods with a completely randomized design (CRD), namely 5 levels of treatment and 3 replications of. P0 (Without injection of batik spinach extract), P1 (Injection of batik spinach extract with a dose of 110 ppm/head), P2 (Injection of batik spinach extract with a dose of 130 ppm/head), P3 (Injection of batik spinach extract with a dose of 150 ppm/head), P4 (Injection of batik spinach extract with a dose of 170 ppm/head). The test animals used were mud crabs (Scylla serrata) with an average initial weight of ±100 grams/head. Animal testing used were 60 mud crabs were used and kept in a plastic basket measuring (59 x 37 x 17) cm3 during 60 days. The results showed that injection of batik spinach extract (Amaranthus bicolor) had a significant effect (P<0,05) on growth, velocity of molting time, amount of molting, specific growth rate, survival rate, but no significant effect (P>0,05) on survival rate of mud crubs. The results showed that the best treatment in accelerating the molting time was P3 with an average of 12,50 days. The highest carapace width growth occured at P3 namely 22,50 mm. Specific growth rate was 0,76% in P3 and the highest survival rate was at P0 100%.